Answer:
g(x) has a greater average rate of change
Explanation:
From the given information, the table is:
x | g(x)
-1 7
0 5
1 7
2 13
From this table, we have g(0)=5 and g(2)=13
The average rate of change over [a,b] of g(x) is given by:
![(g(b)-g(a))/(b-a)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/nfaovqi9ndi106i9vq86fqouyv2rxkggne.png)
This implies that on the [0,2]. the average rate of change is:
![(g(2)-g(0))/(2-0)=(13-5)/(2)=(7)/(2)=3.5](https://img.qammunity.org/2021/formulas/mathematics/middle-school/jy556s08qxjlahpdgk2vupu18p7iq7unpi.png)
Also, we have that: f(0)=-4 and f(2)=-1.
This means that the average rate of change of f(x) on [0,2] is
![(f(2)-f(0))/(2-0)=(-1--4)/(2) =(3)/(2) =1.5](https://img.qammunity.org/2021/formulas/mathematics/middle-school/kc8knqn8e1e5cmk5tbzhtpp3par9b5v310.png)
Hence g(x) has a greater average rate of change on [0,2]